Can financial reporting standards (FRSs) be ameliorated to minimise indiscriminate use of creative accounting? - Ng, Ivy Hui Chen. (2008)
This paper seeks to investigate the feasibility of ameliorating FRSs to minimise indiscriminate use of creative accounting(CA). In the first part of the paper, 20 top ses listed companies are analysed to detect traces of CA. In the second part, proposed changes to FRSs are made.